2017
DOI: 10.3389/fnbeh.2017.00184
|View full text |Cite
|
Sign up to set email alerts
|

Binge-Like Sucrose Self-Administration Experience Inhibits Cocaine and Sucrose Seeking Behavior in Offspring

Abstract: Recent studies show that emotional and environmental stimuli promote epigenetic inheritance and influence behavioral development in the subsequent generations. Caloric mal- and under-nutrition has been shown to cause metabolic disturbances in the subsequent generation, but the incentive properties of paternal binge-like eating in offspring is still unknown. Here we show that paternal sucrose self-administration experience could induce inter-generational decrease in both sucrose and cocaine-seeking behavior, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…As stated above, theta activity has been linked to comparing incoming with expected events 37 , 45 47 , and has been shown to be modulated by the degree of discrepancy between them, that is, by PE. Theta power increase over parieto-occipital regions has been related, for example, to the visual mismatch negativity (vMMN) 57 , an ERP component widely considered as a perceptual PE signal 1 , 6 , 58 , 59 , and the increase observed here could be thus taken as an indicative of higher PE elicited by S2 in the unpredictable condition. Furthermore, P2a and P3 amplitudes were also enhanced.…”
Section: Discussionmentioning
confidence: 71%
“…As stated above, theta activity has been linked to comparing incoming with expected events 37 , 45 47 , and has been shown to be modulated by the degree of discrepancy between them, that is, by PE. Theta power increase over parieto-occipital regions has been related, for example, to the visual mismatch negativity (vMMN) 57 , an ERP component widely considered as a perceptual PE signal 1 , 6 , 58 , 59 , and the increase observed here could be thus taken as an indicative of higher PE elicited by S2 in the unpredictable condition. Furthermore, P2a and P3 amplitudes were also enhanced.…”
Section: Discussionmentioning
confidence: 71%
“…In behavioural studies, we found that TRPA1 antagonism significantly suppressed maintenance of METH IVSA and reinstatement of METH‐seeking behaviour, suggesting that TRPA1 mediates the mechanisms through which METH produces its reinforcing effect. Additionally, considering that inactive lever pressing can be interpreted as an impulsive behaviour that can manifest when readily available drugs become difficult to obtain (Le et al, 2017), the decrease in inactive lever pressing observed with TRPA1 antagonist treatment suggests that TRPA1 inhibition may attenuate METH‐induced impulsive behaviour. Similarly, acquisition of METH‐induced CPP was inhibited by TRPA1 antagonism and was not observed in TRPA1 KO mice, indicating that TRPA1 may play a critical role in METH‐induced rewarding effect.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of a fructose‐rich diet by the father, the mother, or both negatively affects blood pressure, adipokines, and uric acid concentrations of mature offspring, which correspond to markers of elevated cardiovascular risk in progeny 49 . Le et al found that paternal sucrose self‐administration experience results in a decrease in reward‐seeking and induces anxiety‐like behavior in the offspring of rats 50 . Also, paternal HFD and HSD cause significant phenotypic changes in the offspring, including higher body weight, hypothalamic inflammation, altered energy homeostasis, gut microbiota, stress reactivity, and social behavior 51–53 .…”
Section: Effects Of Paternal Diet and Nutrition On Offspringmentioning
confidence: 99%
“… 49 Le et al found that paternal sucrose self‐administration experience results in a decrease in reward‐seeking and induces anxiety‐like behavior in the offspring of rats. 50 Also, paternal HFD and HSD cause significant phenotypic changes in the offspring, including higher body weight, hypothalamic inflammation, altered energy homeostasis, gut microbiota, stress reactivity, and social behavior. 51 , 52 , 53 In a Drosophila model, paternal sugar‐induced intergenerational metabolic reprogramming (lipid metabolism, immune response, obesity, etc.)…”
Section: Effects Of Paternal Diet and Nutrition On Offspringmentioning
confidence: 99%